(untitled) (Orfeu, 2017)
This chapter by Fink-Jensen focuses on two key questions for the development of the pedagogical practice of music students in teacher education: how theory can contribute to the development of practice and how the relationship between theory and practice can be addressed during their education. Regarding the teacher as a researcher she proposes the implementation of a teaching strategy that she called "astonishing practices", relying on anthropological and phenomenological concepts as well as on theories from the field of psychology, pedagogy and music education. The central point is the identification of a problem situation, thus it is essential that the student is able to observe in an open-sensuous way, leaving already established theoretical premises behind so that the student can generate new possibilities for such a teaching situation.